If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 6y + 25 + -3y Reorder the terms: 4 = 25 + 6y + -3y Combine like terms: 6y + -3y = 3y 4 = 25 + 3y Solving 4 = 25 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 4 + -3y = 25 + 3y + -3y Combine like terms: 3y + -3y = 0 4 + -3y = 25 + 0 4 + -3y = 25 Add '-4' to each side of the equation. 4 + -4 + -3y = 25 + -4 Combine like terms: 4 + -4 = 0 0 + -3y = 25 + -4 -3y = 25 + -4 Combine like terms: 25 + -4 = 21 -3y = 21 Divide each side by '-3'. y = -7 Simplifying y = -7
| M^2=66 | | 7t-8-2t+1=23 | | -3x+1=11-x | | -7h-5+3h=-17 | | 0=3x^2+x-5 | | 49p+5=33 | | 0=-2x^2-3x+10 | | 2(x-5)=3(x+1)-3 | | 3x+1y=4 | | .8(.4x+.7)-.2(.5x-.2)=.1x | | x^6-10x^3+16=0 | | G-7+4=-16 | | (2x^2-12)(x^2+7x+12)=0 | | (5x-20)(3x+4)=0 | | 4x(x-1)=19 | | 3=18q | | 2x^4+9x^3+8x^2+9x+2=0 | | -1=-0.6 | | -0.5=15 | | -13=-6-7n | | 1=4x+2 | | 0.4x=0.5 | | 5t^2-4t-25=0 | | 13j=26 | | 123=-5p | | 7s-23=61 | | 2x^3+8x-12=0 | | (x-30)(100-2x)=200 | | -71=2.5x | | 36=.5*b*9 | | 36=.5b*9 | | (10+x)(500-20x)=6000 |